Wells Syndrome Developed After Insect Bite: Case Report and Literature Review - Kaya, Kısmet; Alan, Saadet; Dogmus, Abdurrahman (My University, 2026)
Wells syndrome (eosinophilic cellulitis) is a rare, recurrent inflammatory dermatosis characterized clinically by cellulitis-like erythematous plaques and histopathologically by a dermal eosinophilic infiltrate accompanied by distinctive flame figures. It mainly affects adults. Although the exact pathogenesis remains unclear, it is believed to represent a hypersensitivity reaction to exogenous or endogenous antigens. A variety of triggering factors have been reported, including insect bites, viral infections, autoimmune disorders, malignancies, and certain medications. It commonly presents as a solitary, burning or pruritic erythematous plaque with edema, mimicking acute cellulitis. Systemic corticosteroids are typically the mainstay of treatment; however, in refractory cases, alternative therapies such as dapsone, cyclosporine, and biological agents may be employed. The spontaneous resolution of lesions in some cases makes it challenging to definitively assess the true efficacy of these therapeutic options. Herein, we report a case of recurrent plaque type Wells syndrome in a 35-year-old woman, triggered by an insect bite and remaining undiagnosed for an extended period.
Keywords: Dermatoloji